Credit Risk Management and Entrepreneurship Development in Nigeria: A Case Study of Small and Medium Scale Industries in Ondo State - Kayode, Ogunyemi Joseph; Popoola, Mufutau Akanmu; Adeyinka, Adewole Joseph (International Journal of Small and Medium Enterprises, 2020)
The paper summarizes the arguments and counterarguments within the scientific discussion on credit risk management and entrepreneurship development in Nigeria with focus on small and medium scale industries in Ondo State. The objective of the study is to examine the effect of credit risk management on entrepreneurship development. The study adopted the use of descriptive statistics and regression analysis method to test the hypothesis formulated. The results indicated that entrepreneurship development is being hampered by ineffective credit risk management. The findings has shown that Small Scale Enterprise still suffers greatly from inadequate policy on fund raising, lack of risk management personnel, lack of credit advisory unit in loan houses and Inability to determine appropriate source of funding which significantly affects their level of development. The findings of this study have also found out that the Nigerian markets are filled with numerous business opportunities. Based on the findings, it was recommended that increased government support, uninterrupted power supply and communication link, provision of skilled manpower and computer wizard in operation of payment system, collaboration among banks, provision of adequate security and fight against corruption would assists and improve the growth and development of entrepreneurship in Nigeria.